Psychopathological symptoms as a common Risk Factor for Tinnitus distress and magnitude: a cross-sectional study - Ahmed , Ammar; Naeem Aslam (Journal of the Pakistan Medical Association, 2022)
Abstract Objective: To examine the association of tinnitus distress, tinnitus magnitude and psychopathological symptoms among patients with ear-related problems. Methods: The cross-sectional study was conducted from December 1, 2020, to June 30, 2021, at the Hearing and Balance Clinic, Rawalpindi, Pakistan, in collaboration with the National Institute of Psychology, Quaid-i-Azam University, Islamabad, Pakistan, and comprised adult tinnitus patients of either gender. All patients underwent ear examination and audiological evaluations for tinnitus matching. Psychological assessment was done using the Tinnitus Magnitude Index, the Tinnitus Reaction Questionnaire and the Symptoms Check List-90. Data was analysed using SPSS 21. Results: Of the 159 subjects, 97(61%) were male and 62(39%) were females. The overall mean age was 47.94±17.47 years. Patients showed statistically significant tendency to develop psychopathological symptoms, including somatisation, phobic anxiety, depression and paranoid ideation (p<0.05). Additionally, significant gender differences were also observed (p<0.05). Conclusion: There was a high prevalence of tinnitus distress along with psychopathological symptoms among tinnitus patients. Key Words: Tinnitus, Psychopathology, Gender, Cross-sectional study.